Evaluasi Keamanan Jembatan Terhadap Gerusan Lokal: Studi Kasus Pada Jembatan Sumanda - Sukamulya Tanggamus, Lampung - Suharni, Suharni; Wahono, Endro Prasetyo; Kusumastuti, Dyah Indriana; Zakaria, Ahmad; Purwadi , Ofik Taupik (Universitas Nahdlatul Ulama Blitar, 2025)
Bridges represent a vital component of strategic infrastructure, facilitating the movement of traffic and the distribution of logistics. Bridges facilitate connectivity between disparate geographical regions. It is of the utmost importance to prevent damage and failure of bridge structures. Bridge structure failure is the formation of local scour at the pillars and abutments of the bridge. The objective of this research is to assess the safety of the Way Sumanda-Sukamulya Bridge in regard to the potential for scour at the pillars and abutments. Topographic surveys, instantaneous discharge, and riverbed sediment gradation were conducted for the purpose of collecting data regarding the potential for scour. Ten years of rainfall data were obtained from the Mesuji-Sekampung BBWS, which served to corroborate the design flood discharge. An evaluation of scour was conducted using the HEC-RAS 1D. The scour depth at the pillars ranged from 1.60 m to 1.89 m, while the scour depth at the abutments reached 2.28 m to 3.17 m. It was observed that the outer bend of the river presented a greater scour depth than the inner part. It is imperative that the Way Sumanda Bridge be periodically assessed to ensure that the risk of local scour is kept to an absolute minimum.